Personality-Related Factors and Depressive Symptomatology Predict Behavioral Control in Patients With Alcohol Use Disorders - Lebiecka, Zofia; Skoneczny, Tomasz; Tyburski, Ernest; Samochowiec, Jerzy; Jędrzejewski, Adam; Wirtz, Janina; Kühn, Simone; Nielsen, Anette Søgard; Mellentin, Angelina Isabella; Michelis, Leonie Ascone; Kucharska-Mazur, Jolanta (Frontiers in Psychiatry, 2022)
In the face of increasing social, economic and health consequences of alcohol use disorders (AUDs) and limited effects of available treatment options, the search for novel prevention and management methods continues to remain a timely and valid endeavor. This, however, requires a better grasp of the theoretical framework underlying addiction mechanisms. With the goal to extend the existing body of evidence on AUDs, we set out to investigate the effect of personality-related factors and depressive symptomatology on i) impulsivity, ii) cognitive response inhibition, and iii) the links between the two measures of behavioral control (different facets of impulsivity and response inhibition) in a treatment-seeking AUD sample. To this end, 53 male (n = 45) and female (n = 8) inpatients at an alcohol rehabilitation center completed three self-report questionnaires: the International Personality Item Pool (IPIP-50), the Beck Depression Inventory Second Edition (BDI-II) and the Barratt Impulsiveness Scale (BIS-11) and performed one behavioral task - an alcohol go/no go task. Regression analyses revealed conscientiousness, intellect, and depression level to be important potential predictors of self-report impulsivity and processing speed in recovering drinkers. No significant links were observed between the two measures of behavioral control, thus complementing evidence that while they both encompass behavioral under-regulation, they may indeed represent distinct psychological constructs.